MORPHOLOGICAL AND FUNCTIONAL CHARACTERISTICS OF PLACENTA IN PREGNANT WOMEN WITH THYROTOXICOSIS - Afanasiev, I.V.; Paraschuk, Yu.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
30 pregnant women research with normal function of thyroid gland and 30 pregnant women with thyrotoxicosis.Morphological research of placenta with using histochemical and stereometrical methods.It was revealed features of chronicle placental insufficiency on the background of chorion vascularisation disturbances, reinforcement of involutive and sclerotic processes in pregnant women with thyrotoxicosis. Thyrotoxicosis in pregnancy caused disturbances maturation of villous chorion, which leads chronicle placental insufficiency. Thus,  thyrotoxicosis complicates current of pregnancy and requires prescription of adequate therapy.